Effect of cut-off walls on submarine groundwater discharge in non-isothermal conditions - Tianyuan ZHENG; Xiao XIN; He WANG; Shaobo GAO; Lecheng LIU; Bo ZHANG; Xilai ZHENG; Jian LUO (Shuiwen dizhi gongcheng dizhi)
Temperature could change the migration characteristics of coastal groundwater. However, research on groundwater discharge processes under the influences of cut-off walls has been limited to isothermal conditions. This study built a two-dimensional numerical model coupling groundwater flow and salt transport in non-isothermal conditions at the site scale to investigate the impact of cut-off walls on groundwater discharge processes, considering the thermal effect. We focused on the dynamic characteristics of submarine groundwater discharge in non-isothermal conditions which are common in reality. This research quantitatively assessed the influence of seawater temperature on groundwater discharge flux (Q) and relative discharge flux (Q'). The results indicate that, under high-temperature seawater conditions, the timescale for Q' to reach equilibrium is significantly reduced. Specifically, higher freshwater temperatures and lower seawater temperatures could result in a greater Q'. However, when the seawater temperature exceeded the groundwater temperature by 15°C, reverse circulation is more likely to develop in the saltwater zone, which accelerates groundwater circulation and increases the total groundwater discharge into the sea, resulting in a corresponding rise in the Q' value. This study is significant for cut-off wall structure optimization and coastal groundwater sustainable utilization.